Organizing Art and Culture Management Practices in a Public School - Rezende, Bruno; Faustino Júnior, Dério (Organizações & Sociedade, 2023)
This paper aims to analyze the organizing of art and culture management practices in a federal education institute. To that end, we utilize the contributions of two epistemological approaches, organizing and the practice lens. The study is characterized as qualitative research, developed in two main steps: an exploratory step, which involves the analysis of documents and two projective interviews; and a field immersion step, characterized by participant observation and by the analysis of management practices in the implantation of an Art and Culture Nucleus at the studied institute. As a result, an organizing approach articulated with art and culture management practices enables one to understand school management in a less orthodox manner in opposition to the usual binarism of the school management research field, which involves the disputes between elements and ideologies of the traditional school management and the democratic school management approaches. The study contributes by characterizing the process of re-signification of material aspects in the practice of school management, which makes it possible to problematize the use of administrative planning and the role of contextuality in the attribution of competences of group dynamics, and to point out the effects of decision-making in school management.